Factors affecting institutional transformation for regulated MFIs - Ndulu, John Kimuli; Kiweu, Josephat Mboya (My University, 2015)
Purpose - Regulating microfinance activities has been an important policy concern in improving financial inclusion and extending financial services to all. However, introducing a regulatory framework of any kind pushes targeted institutions to change. In this case, microfinance regulatory framework in Kenya that came to effect in 2008 has created three tiers of microfinance institutions: prudentially regulated deposit-taking institutions, credit only and unregulated informal groups. Those undertaking deposit-taking business were required by this regulation to transform their operations to comply with the requirements. Though many institutions wanted to be allowed to mobilise public deposits, only six institutions had managed to obtain a license in four years after the regulation became operational. The purpose of this research was to establish the factors affecting this microfinance transformation process. Design/methodology/approach – The research was carried out by collecting empirical evidence from microfinance institutions target by regulation in Kenya to establish these factors contributing to the slow phase of transformation. The possibility that the challenges could be affecting both the regulator and institutions being regulated was explored. Findings – This study identifies several important factors affecting the transformation process of microfinance institutions in Kenya. These include the ability to meet capital requirements, restructuring existing ownership and getting new shareholders, ability to raise funds for transformation, acquiring suitable information systems, motivation to be regulated, governance issues and managerial inertia. These factors explain why certain institutions have moved faster than others in the transformation process and why some have opted to remain credit only Research limitations – The availability of reliable database of microfinance institutions that were a target for this study was a challenge affecting sampling and reach. In addition, data collected was limited to one point of contact yet some factors could relate to operational process. Originality/value – The study broadens research to transformation process of regulated microfinance institutions, factors affecting them and regulatory framework